Forest loss and management in land reform settlements: implications for REDD governance in the Brazilian Amazon - Ezzine-de-Blas, D.; Borner, J.; Violato-Espada, A.L.; Nascimento, N.; Piketty, M.G. (2011)
Land reform settlements (LRS) in the Brazilian Amazon have been suggested to hold promise for the successful implementation of incipient efforts to reducing emissions from deforestation and degradation (REDD). However, differences in forest cover, deforestation behav- iour and settler welfare plus the inevitable overlap of upcoming REDD efforts with existing conservation policies, mean that scope and impact of REDD in LRS will not be uniform across settlements. Based on evidence from a case study of four LRS and a Brazilian Amazon regional analysis of opportunity costs, this paper explores the actual scope for targeting initial Brazilian REDD efforts to LRS and discusses potential welfare and equity implications based on scenario analysis. While our findings confirm considerable economic scope for compensation-based schemes for avoided degradation and deforestation, the pre-existence of legal use right limitations in combination with the distribution of forest cover among LRS means that less than half of settlements – poorer – will be able to derive economic gains. Exploring a mix between incentives and disincentives seems to offer the most promising future regarding efficiency and equity successful results. The paper concludes with the implications of the results in the international debate on the constraints ahead to imple- ment the REDD principles.